World as Sediments - Tavakol, Reza (Cosmos and History: The Journal of Natural and Social Philosophy, 2025)
Sediment as a concept and metaphor has been employed to characterise a large variety of processes and structures, ranging in nature from material, to social and conceptual. The prototypical notion of sediment used in such characterisations often mirrors that of geological sediments. Despite their variety and ubiquitousness here on Earth, geological sediments are unduly restrictive and special in nature. In particular, they are solid, fossilised, layered and no longer in a continued state of formation. Here I consider the concept of sediments from a wider, cosmological, perspective by treating them as spatiotemporal outcomes of interrelated nonlinear dynamical processes, on vast scales of space and time. Such sediments are generally non-solid, non-fossilised, ongoing and able to impact the processes that are giving rise to them. They can take multitudes of forms, including sediments that are not accumulative/additive and layered as in the case of geological sediments, but subtractive and/or non-layered/dispersive or a combinations of these — as well as others that are in principle closed to observers, such as black holes. There are also sediments which are non-material, such as those in electromagnetic fields (light), including those that are manifestly spatiotemporal. Seen from this perspective the observable Universe could be looked upon as an enormously complex and interrelated web of diverse and novel sedimentary processes and structures coming into being and withering away — often involving chaos and contingency and at times undergoing cataclysmic metamorphosis, which could in the process drastically impact the environments that gave rise to them, altering their future histories. They generally possess multiple origins and can occur on vast range of scales of space and time, extending from the beginnings of the Universe soon after the Big Bang to its very far future, which is presently unknown, including ourselves as biological beings and observers. The concept of sediment has also been used as a metaphor to conceptualize various social and conceptual constructs, such as geometrical concepts — which as we shall see can also be extended to the case of Mathematics as a whole. A key distinguishing feature of sediments is how they relate to time, not only in terms of their lifetimes, which can take a vast range, including sediments with lifetimes enormously longer than the present age of the Universe, as well as mathematical sediments that appear future eternal — but importantly also by the way they encode time: explicitly (as in layered sediments), implicitly (as in non-layered dispersive sediments), and implicitly with ruptures (as in cataclysmic sediments). The generalised notion of sediment introduced here provides a far richer framework to conceptualise the sedimentary concept and metaphor in enormously diverse settings, while emphasising the interconnectedness of sediments, their multiple origins, as well as their ongoing, potentially cataclysmic and contingent natures. It also raises fundamental questions regarding their ultimate fates in a transient Universe.